2004
DOI: 10.1542/peds.113.6.1700
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Depressive, and Posttraumatic Stress Disorders Among Mothers of Pediatric Survivors of Hematopoietic Stem Cell Transplantation

Abstract: A subset of mothers of children who survive HSCT may require psychological intervention. Mothers who are most at risk are younger and evidence anxiety and depressive symptoms at the time of transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
87
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 55 publications
8
87
2
Order By: Relevance
“…Maternal age (younger) has been previously identified as a risk factor for psychopathology in this population. 16 Young mothers who care for very ill children may have limited personal and external resources to address the multiple stressors related to their child caring role, which may increase their risk for psychological distress. In contrasting, older fathers who, before the child's illness, may have been less involved in childcare than mothers 3 may cope differently than mothers when taking child-caring responsibilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal age (younger) has been previously identified as a risk factor for psychopathology in this population. 16 Young mothers who care for very ill children may have limited personal and external resources to address the multiple stressors related to their child caring role, which may increase their risk for psychological distress. In contrasting, older fathers who, before the child's illness, may have been less involved in childcare than mothers 3 may cope differently than mothers when taking child-caring responsibilities.…”
Section: Discussionmentioning
confidence: 99%
“…15 A small percentage of mothers have been diagnosed with major depression, posttraumatic stress and generalized anxiety 18 months post SCT, with younger mothers presenting the highest symptoms at pre-SCT. 16 The longitudinal studies addressing parental distress after SCT are mainly for mothers. [17][18][19][20][21] In summary, the current literature is inconclusive regarding parental gender differences and psychological distress, and related factors after pediatric SCT.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that parents of children undergoing SCT can suffer from posttraumatic stress symptoms [25,27], depression [6,26], distress [35,39], and anxiety [6,25]. Maternal post-SCT anxiety and depression scores have been found to correlate with their children's QoL ratings at 6 months post-SCT [6].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 20% of mothers had clinically significant PTSD spectrum symptoms. This prevalence increased to nearly one third when subthreshold PTSD was included [17].…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 98%